Contribution of cannabis-related cues to concurrent reinforcer choice in humans. (1st June 2019) - Strickland, Justin C.; Lile, Joshua A.; Stoops, William W.
Highlights: We evaluated the impact of cannabis cues on concurrent choice behavior. A cannabis history group showed significant bias for cannabis-cued choices. Cannabis choice was associated with cannabis use frequency and demand. Cannabis cues can alter decision-making processes for non-drug reinforcers. Abstract: Background: Drug-related cues play a critical role in the development and persistence of substance use disorder. Few human laboratory studies have evaluated how these cues contribute to decisions between concurrently presented reinforcers, and none have examined the specific role of cannabis cues. This study evaluated the contribution of cannabis-related cues to concurrent monetary reinforcer choice in humans. Methods: Participants with a cannabis use history (i.e., use in the past two weeks and 50 or more lifetime uses; n = 71) and controls without this history (i.e., 5 or less lifetime uses; n = 79) were recruited using Amazon Mechanical Turk. A cued concurrent choice task was used in which cannabis trials presented two cues (one cannabis and one neutral) side-by-side followed by concurrent monetary offers below each image. The primary dependent measure was choice for cannabis-cued monetary reinforcers on equal value trials. Secondary analyses evaluated individual difference variables related to choice bias. Results: Participants in the cannabis group showed a significant bias for cannabis-cued choices (mean 76.0%) whereas participants in the control group showed a significant bias against cannabis-cued choices (mean 30.3%). Reaction times on cannabis trials were faster than neutral filler trials and did not differ by group. Cannabis-cued choice was significantly associated with more frequent cannabis use ( r = .44), higher cannabis demand intensity ( r = .28), and lower cannabis elasticity ( r = -.30). Conclusions: These findings suggest that cannabis-related cues can influence reinforcer choice and potentially promote disadvantageous decision-making related to non-drug reinforcers.